Digital Transformation Process in the Profitability of a Medicine Distribution Company, Trujillo – 2024 - Ninatanta Alva, Jorge Humberto (2025)
The general objective of the study was to establish the influence of digital transformation on the profitability of a pharmaceutical distribution company in Trujillo, 2024. The research employed a quantitative, non-experimental, cross-sectional, and explanatory approach. The population consisted of 96 employees of the company, and a probabilistic sample of 78 participants was obtained through random selection. Questionnaires with ordinal scales were used. A descriptive and correlational analysis was conducted using SPSS software version 26. The results showed a moderate (0.756) and significant relationship, with a 99% influence between digital transformation and profitability. Process digitization (0.731) influenced profitability by 59%, improvement in customer experience (0.513) by 62%, business model innovation (0.714) by 64%, and optimization of the value chain (0.670) by 64%. It is concluded that digital transformation influences the company's profitability, with business model innovation and value chain optimization being the most influential factors.